The Family Decision Making Patterns of Children with Special Needs: a Sociology Study of the Family - Azis, Fatimah; Mukramin, Sam'un (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2020)
This study aims to explain information about the patterns of family decision making for parents who have children with special needs in the city of Makassar. This type of research is descriptive qualitative. The results of the study show that parents are key figures who play a very important role in providing role models, guidance, and affection in the process of child development. The role of parents in the acceptance of children with special needs is very important. Parents are the best guides and helpers for the independence of children with special needs. The mother as one of the parents of children with special needs has an important role in understanding the needs and development of their children. This is related to the mother's acceptance of children with disabilities, which is shown in the attitude to face children. If parents lack understanding of children with special needs, it can result in a lack of attention and consider the child to be unlucky in the family. Parents are the determinants of a child's life before and after birth. Therefore, it is the responsibility of parents to fully accept the existence of their children and treat them equally in all aspects of life with children in general without any discriminatory attitude and to provide the widest possible opportunity for education.